Role of small interfering RNA (siRNA) in targeting ocular neovascularization: A review - Supe, Shibani; Upadhya, Archana; Singh, Kavita (Experimental eye research, 2021)
Ocular neovascularization (NV) plays a central role in the pathogenesis of various ocular diseases including diabetic retinopathy, age-related macular degeneration, retinoblastoma, retinitis pigmentosa and may lead to loss of vision if not controlled in time. Several clinical trials elucidate the central role of vascular endothelial growth factor (VEGF) in the pathogenesis of the ocular neovascularization. The advent and extensive use of ocular anti-VEGF therapy heralded a new age in the treatment of retinal vascular and exudative diseases. RNA interference (RNAi) can be used to inhibit the in-vitro and in-vivo expression of specific genes and thus provides an extremely useful method for investigating gene activity with minimal toxicity. siRNA targeting VEGF overcomes many drawbacks associated with the conventional treatment available for the treatment of ocular neovascularization. However, delivery methods that protect the siRNA against degradation and are appropriate for long-term care will help increase the effectiveness of RNAi-based anti-VEGF ocular therapies. Several nanotechnology approaches have been explored by formulation scientists for delivery of siRNA to the eye; targeting particularly VEGF for the treatment of NV. This review mainly focuses on current updates in various pre-clinical and clinical siRNA strategies for targeting VEGF involved in the development of ocular neovascularization. •Ocular NV plays a central role in the pathogenesis of various ocular diseases.•Ocular NV is usually associated with loss of vision in diabetic retinopathy and age-related macular degeneration.•VEGF and its isoforms are recognized as the principal targets for the treatment of ocular NV.•siRNA strategies to downregulate VEGF are being explored.•Several nanotechnology approaches are employed for the delivery of VEGF siRNA in the treatment of ocular NV.